PENGARUH PEMANFAATAN DAN PENGGUNAAN SISTEM INFORMASI TERHADAP KINERJA INDIVIDU (Studi Kasus pada Perum BULOG Divisi Regional Jawa Tengah) - Wedha Achmad Hartono; Wahyu Meiranto (Diponegoro Journal of Accounting, 2013)
The development of information technology enables the society to perform various activities better and easier. The activities include organization and business aspects. Information technology is used to improve the performance of individuals as members of a business organization which in turn is expected to increase the performance of the organization. The determinants of the effectiveness of information systems are the acceptance and the behavioral use of information technology in a company's accounting system.The aim of this study was to determine the effects of performance expectancy, effort expectancy, and social influence on the behavioral intention, as well as the effects of facilitating conditions and behavioral intention on use behavior. The research was conducted by distributing and collecting questionnaires of 70 employees of Perum BULOG Regional Division of Central Java as the respondents. The questionnaires used in this research were 60. Descriptive analysis was used in the analysis of average, median, range, and standard deviation of the independent variables, while analysis of the hypothesis was conducted by using Partial Least Square (PLS).The results showed that performance expectancy and effort expectancy had no positive effect with intention of information system. Meanwhile, social influence has positive effect with intention of information system. Facilitating conditions had positive effect with information system usage, while intentionof information system had no positive effect with information system usage.